Privacy and security challenges in smart and sustainable mobility - Paiva, Sara (2022)
The current era of computing is witnessing a huge amount of data being generated with every passing moment. This massive data if nourished efectively can open new horizons for the computing world. The modern world is slowly but surely moving towards the automation age where every entity and object is being automated to perform desired tasks without the need of human interventions. This has made the lives of people more convenient and comfortable. Automation has taken over every single feld of computing and even beyond. Smart mobility is one such example of automation wherein the users get real time information about the trafc conditions as well as alternate route suggestions in case of trafic jams. Transportation is considered as the backbone of every business. The automated intelligent transportation system (ITS) has completely transformed the way how people, goods and services are transported and is quite important for achieving sustainability. This paper provides an overview of the existing ITS system, concept of smart mobility and existing vulnerabilities in these systems. Their security concerns and scenarios are also analyzed. Furthermore, in this paper the importance and need for securing these intelligent systems is highlighted and future trends in ITS is also suggested. Although ITS and smart mobility technology are already providing convenient transportation and navigational facilities, there is still a huge scope to improve these facilities for the end users. The suggested future trends if integrated in an efective manner can provide exemplary means to provide state-of-the-art navigational facilities and smart mobility in a true sense.